Comparison of Infection Rates in Diabetic versus Non-Diabetic Patients after Elective Surgical Procedures - Ghani, Usman; Ashraf, Muhammad Ayub; Malik, Muhammad Jalil; Zulfiqar, Mujahid; Haq, Qazi Tafheem ul; Usman, Tayyaba (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency of surgical sites infections in diabetic vs. non-diabetic patients after elective surgical procedures. Study Design: Quasi-experimental study. Place and Duration of Study: Department of General Surgery Combined Military Hospita, Lahore, Pakistan from Jul 2022 to Jun 2023. Methodology: Patients aged 20 to 70 years who underwent elective foot and ankle surgeries totaled 210 and were eligible for inclusion in the study. Diabetic patients were assigned to Group A, whereas non-diabetic patients were assigned to Group B. Each patient was observed for the occurrence of surgical site infection. Results: Gender distribution revealed that 54.3% of patients were male, while 45.7% were female. The mean age of patients was 46.00±5.90 years. The mean BMI was 25.03±2.25 kg/m2. The average durations of surgery and hospital stay were 1.15 hours and 8.14 days, respectively. Among diabetic patients, the mean duration of diabetes was 12.08±3.84 years, and the mean HbA1c level was 7.64±2.03. Among diabetic patients, 14 cases (13.3%) developed infections, while in the non-diabetic group, 8 cases (7.6%) were observed. Conclusion: In conclusion, our study demonstrated a notable disparity in the incidence of surgical site infections (SSIs) between diabetic and non-diabetic patients undergoing elective surgical procedures. With 13.3% of diabetic patients experiencing SSIs compared to 7.6% in the non-diabetic group, these findings emphasize the heightened vulnerability of diabetic individuals to postoperative complications.